Penggunaan Bahan Alam untuk Melatih Kreativitas Peserta Didik dalam Kegiatan Mewarnai di TK PKK 27 Jambean - Hikmawati, Hikmawati; Takasun, Takasun; Purwati, Sri (BALE LITERASI, 2021)
Creativity is one of the competencies that must be possessed by students in the 21st century. These competencies need to be trained from an early age. The creativity of students in coloring activities at PKK 27 Jambean Kindergarten is still not optimal. The purpose of this community service activity is to train the creativity of students in Jambean PKK Kindergarten through coloring activities using natural materials. The method of implementing community service activities is carried out through three stages, namely planning, implementation, and evaluation. This activity was attended by group B students with an age range of 5 to 6 years, a total of 7 people. The activity was carried out for 10 days from November 15 to 25, 2021. At the planning stage, the team prepared learning tools and coordinated with the Principal and parents/guardians of students. At the implementation stage, the team trained the creativity of students in coloring butterflies using natural materials. At the evaluation stage, the team discusses the results of the training activities and plans for follow-up. he results of the activity show that students can use tools to take charcoal well. Students can draw the shape of a butterfly by thickening the butterfly sketch using wood charcoal properly. Students can color the butterfly that has been thickened and then colored with turmeric and young teak leaves and telang flowers well. The use of natural materials in coloring activities makes students more enthusiastic, serious, and happy about learning. The use of natural materials for coloring can be used by teachers or students not only on the animal theme, but also on other themes such as plants and fruits.